Iron Deficiency Anemia in Children and Adolescents: Epidemiology, Risk Factors, Clinical Manifestations, Diagnosis, Treatment, and Prevention - Mohammad Koblan Abedraboh Alshwawreh; Nader Emad Mousa Hijazeen (SAS Journal of Medicine, 2026)
Iron deficiency anemia (IDA) is the most common nutritional deficiency and the leading cause of anemia worldwide, affecting infants, children, and adolescents disproportionately. IDA remains a significant public health concern because of its high prevalence and its potential impact on growth, neurodevelopment, cognitive function, physical performance, and quality of life. The etiology of pediatric IDA is multifactorial and includes inadequate dietary iron intake, increased iron requirements during periods of rapid growth, chronic blood loss, and impaired intestinal iron absorption. Clinical manifestations vary according to age and disease severity and may range from asymptomatic iron deficiency to fatigue, pallor, impaired cognitive performance, behavioral disturbances, and reduced physical capacity. Diagnosis relies on clinical assessment and laboratory investigations, including complete blood count and iron studies, with serum ferritin serving as the most sensitive indicator of iron deficiency. Oral iron replacement therapy remains the first-line treatment for most children, while intravenous iron is reserved for selected cases. Prevention strategies include optimization of maternal iron status during pregnancy, delayed umbilical cord clamping, appropriate infant feeding practices, iron supplementation for high-risk groups, and routine screening of susceptible populations. Early recognition, timely intervention, and effective preventive measures are essential to reduce the burden of IDA and its long-term consequences in pediatric populations.